Research in personnel and human resources management - Buckley, M. Ronald; Wheeler, Anthony R.; Halbesleben, Jonathon R. B. (Research in personnel and human resources management ;, 2017)
Volume 35 of Research in Personnel and Human Resources Management will contain six chapters on salient issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field. The subject matter in this volume covers employment barriers, mentoring relationships, authentic leadership, emotion regulation and workplace deviance and performance management.